Pelatihan Kepemanduan Wisata Lokal dan Pengelolaan Konten Media Sosial pada Pelaku Wisata Komunitas Batik Kota Bekasi (KOMBAS) untuk Meningkatkan Promosi Budaya: Local Tour Guideance Training and Social Media Content Management for Tourism Actors in the Koperasi Batik Kota Bekasi (KOMBAS) to Improve Cultural Promotion - Fitriyani, Lamria Raya; Rachmawati, Dewi; Wibowo DC, Yesi Pandu Pratama (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The existence of Bekasi City Batik, which has been around since 2014, is not yet widely known by the wider community, even by the people of Bekasi City themselves. For this reason, this community service activity aims to increase the capacity of tourism actors who are members of the Bekasi City Batik Community (KOMBAS) through training local tour guides and managing interactive content on social media. This activity is designed to optimize the potential of batik tourism as a local cultural asset as well as to increase public awareness of Bekasi City Batik so that it can reach a wide range, not only the people of Bekasi City but also the archipelago and is even expected to be global. The method used in this community service is in the form of direct or face-to-face offline training, then a simulation of tour guiding practices through storytelling is also carried out, as well as the practice of creating and managing interesting and interactive social media content. The results of the community service program carried out showed that participants were enthusiastic about participating in the training and there was an increase in knowledge and skills for each training of 40 % for local tour guide training and 20% for social media content training. It is hoped that the two trainings provided to members of the Bekasi City Batik Community (KOMBAS) can be implemented so that they can increase tourism in Bekasi City and also increase public awareness of Bekasi City Batik.